STIMULASI KEMAMPUAN PRA-MENULIS MELALUI AKTIVITAS “CERIA” PADA ANAK DENGAN DOWN SYNDROME DI TK IT AS- SALAM KOTA MALANG - Yauma Ainaya Fitri; Ajeng Putri Pratiwi (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study aims to describe the implementation of "Ceria" Activities (Creative Pre-Writing Activities) in stimulating pre-writing skills of children with Down syndrome at TK IT As-Salam Malang City and to identify the challenges faced during its implementation. This study employed a qualitative approach with a case study design. Research was conducted from April 20 to May 8, 2026, at TK IT As-Salam Malang City, involving one child with moderate Down syndrome as the research subject. Data were collected through observation using a checklist instrument, interviews with classroom and shadow teachers, and documentation. Data were analyzed using the Miles model through data reduction, data presentation, and conclusion drawing, supported by source and technique triangulation. The findings revealed that "Ceria" Activities, encompassing drawing with an image-completion technique, beading (meronce), finger painting, and puzzle, contributed to the development of the child’s pre-writing readiness through the stimulation of fine motor skills, hand-eye coordination, object manipulation abilities, sensory responses, and hand movement control. In addition, these activities also stimulated the sensory integration system, particularly the tactile system through activities involving various textures, the vestibular system through activities involving balance and body movement coordination, and the proprioceptive system through the use of muscles and joints when grasping, pressing, and moving objects. Implementation was carried out gradually, repeatedly, and adaptively according to the child's condition. Key challenges identified included mood instability, short attention span, dependency on teacher assistance, and limitations in visual-motor coordination.